Anisotropias magnéticas em filmes finos de Co: uma análise por magnetometria de torque - Rigue, Josué Neroti (2010)
By studying the magnetic behavior of materials a very important parameter to be analyzed are the constants of anisotropy. They can be associated with an effective anisotropy energy or to a more specific one as, for example, the magnetocrystalline. During the thin films deposition by magnetron sputtering, an uniaxial effective anisotropy can be induced due to the presence of a magnetic field over the sputtering guns and the relative motion of the substrate. However, several additional factors may control the anisotropy, including the film thickness, composition and substrate. In this work, two set of Co samples were grown by magnetron sputtering, with thickness ranging from 50 Å to 500 Å. The difference between the set of samples is the substrate, glass or Si(111). In order to study the magnetic anisotropy in these samples a torque magnetometer was developed. The study has shown that for both set of samples the uniaxial anisotropy, induced in the growth procedure, is the main one for the thicker samples. Above some thickness the samples present just uniaxial anisotropy, 230 Å and 400 Å for samples grown over glass and Si, respectively. Below these thicknesses, for both set of samples, the interaction with the substrate promotes the appearing of a biaxial and, less intense, triaxial anisotropies. The origin of these anisotropy terms are, probably, from magnetoelastic interaction with substrate and magnetocrystalline. Also, it was made an investigation of the surface s morphology and crystalline structures of the studied samples.